The effects of progressive resistance training combined with a whey-protein drink and vitamin D supplementation on glycaemic control, body composition and cardiometabolic risk factors in older adults with type 2 diabetes: study protocol for a randomized controlled trial - Daly, R.; Miller, E.; Dunstan, D.; Kerr, Deborah; Solah, Vicky; Menzies, D.; Nowson, C. (BioMed Central, 2014)
Background - While physical activity, energy restriction and weight loss are the cornerstone of type 2 diabetes management, less emphasis is placed on optimizing skeletal muscle mass. As muscle is the largest mass of insulin-sensitive tissue and the predominant reservoir for glucose disposal, there is a need to develop safe and effective evidence-based, lifestyle management strategies that optimize muscle mass as well as improve glycaemic control and cardiometabolic risk factors in people with this disease, particularly older adults who experience accelerated muscle loss. Methods/Design - Using a two-arm randomized controlled trial, this 6-month study builds upon the community-based progressive resistance training (PRT) programme Lift for Life® to evaluate whether ingestion of a whey-protein drink combined with vitamin D supplementation can enhance the effects of PRT on glycaemic control, body composition and cardiometabolic health in older adults with type 2 diabetes. Approximately 200 adults aged 50 to 75 years with type 2 diabetes, treated with either diet alone or oral hypoglycaemic agents (not insulin), will be recruited. All participants will be asked to participate in a structured, supervised PRT programme based on the Lift for Life® programme structure, and randomly allocated to receive a whey-protein drink (20 g daily of whey-protein plus 20 g after each PRT session) plus vitamin D supplements (2000 IU/day), or no additional powder and supplements. The primary outcome measures to be collected at baseline, 3 and 6 months will be glycated haemoglobin (HbA1c) and insulin sensitivity (homeostatic model assessment). Secondary outcomes will include changes in: muscle mass, size and intramuscular fat; fat mass; muscle strength and function; blood pressure; levels of lipids, adipokines and inflammatory markers, serum insulin-like growth factor-1 and 25-hydroxyvitamin D; renal function; diabetes medication; health-related quality of life, and cognitive function. Discussion - The findings from this study will provide new evidence on whether increased dietary protein achieved through the ingestion of a whey-protein drink combined with vitamin D supplementation can enhance the effects of PRT on glycaemic control, muscle mass and size, and cardiometabolic risk factors in older adults with type 2 diabetes.